2003
DOI: 10.1016/s0928-8244(03)00208-6
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the O-polysaccharide ofProteus penneri28 andProteus vulgarisO31 and classification ofP. penneri26 and 28 inProteusserogroup O31

Abstract: The lipopolysaccharides (LPS) of Proteus penneri 28 and Proteus vulgaris O31 (PrK 55/57) were degraded with dilute acetic acid and structurally identical high-molecular-mass O-polysaccharides were isolated by gel-permeation chromatography. Sugar analysis and nuclear magnetic resonance (NMR) spectroscopic studies showed that both polysaccharides contain D-GlcNAc, 2-acetamido-2,6-dideoxy-L-glucose (L-2-acetamido-2,6-dideoxyglucose (N-acetylquinovosamine)) and 2-acetamido-3-O-[(S)-1-carboxyethyl]-2-deoxy-D-glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The Proteus O31 serogroup is divided into two subgroups: O31a for P. penneri 2692 and O31a,b for P. penneri 28, S29, R15 and P. vulgaris PrK 55/57. [93][94][95] The OPSs of both subgroups are linear and have trisaccharide O-units containing one L-QuiNAc and two GlcNAc residues. The OPS of subgroup O31a,b is distinguished by etherification of one of the GlcNAc residues with (S)-lactic acid giving rise to N-acetylisomuramic acid (Fig.…”
Section: 146mentioning
confidence: 99%
See 1 more Smart Citation
“…The Proteus O31 serogroup is divided into two subgroups: O31a for P. penneri 2692 and O31a,b for P. penneri 28, S29, R15 and P. vulgaris PrK 55/57. [93][94][95] The OPSs of both subgroups are linear and have trisaccharide O-units containing one L-QuiNAc and two GlcNAc residues. The OPS of subgroup O31a,b is distinguished by etherification of one of the GlcNAc residues with (S)-lactic acid giving rise to N-acetylisomuramic acid (Fig.…”
Section: 146mentioning
confidence: 99%
“…As little OPS domain in common as a single 3substituted b-D-GlcpNAc residue is sufficient for providing a cross-reactivity between P. mirabilis O23 antiserum and the LPSs of P. mirabilis O6, 31 as well as between P. vulgaris O22 antiserum and the LPS of P. penneri O59 and O61. 72 Cross-reactive minor epitopes are often associated with more complex monosaccharide derivatives, such as N-acetylisomuramic acid (O31 and O64a,b,d 92,94 ), GlcNAc6PEtn (O16, O17 and O67 59,64 ), an amide of GalA with L-lysine (O3, O26 and O28 84 ), or ribitol 5-phosphate (O33 and O73a,73b 98,148 ). A marked serological cross-reactivity of P. mirabilis O7 and O49 LPSs 32 was evidently due to the presence of similar negatively charged N-acyl derivatives of Qui4N with malonic and succinic acid, respectively.…”
Section: Serological Cross-reactivity Of Proteus O-antigensmentioning
confidence: 99%
“…O-polysaccharide-specific immunoglobulins were eliminated from the serum by its adsorption with an alkali-treated LPS of P. vulgaris 55/57 (O31a,b) containing the OPS structurally identical to P. penneri 28 OPS and a different core region serotype [21]. A lack of reaction with P. vulgaris 55/57 LPS indicated that all antibodies specific to the OPS were completely removed from the serum (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The reactivity of the tested antiserum was checked by ELISA with a set of forty-one Proteus sp. LPSs selected on the basis of the results of previous serological studies conducted in the Department of General Microbiology (Zych et al, 2000;2005;Sidorczyk et al, 2002a;Kondakova et al, 2003;Drzewiecka et al, 2004). The coreantiserum reacted with seven LPSs.…”
Section: Resultsmentioning
confidence: 99%